Perlindungan Hukum bagi Streamer yang Dijadikan Sarana Promosi Judi Online melalui Fitur Donasi - Lumbantoruan, David; Yuniawaty, Yenny (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The misuse of the donation feature on streaming platforms as a means of promoting online gambling shows a deviation from the original function of the feature, which should be a place for appreciation and voluntary support for streamers. This phenomenon raises legal issues because the practice of promoting online gambling is carried out through donation mechanisms in various ways, such as inserting hidden promotional messages, using account names related to gambling, and sending repeated donations as spam. This situation causes streamers to suffer moral, social, and legal harm, thus necessitating legal protection for streamers who are used as a means of promoting online gambling through the donation feature. This study uses a normative juridical method with a legislative and conceptual approach. The nature of the research used is descriptive and analytical. In this study, the author uses secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The misuse of the donation feature on streaming platforms is generally carried out by promoters who join live broadcasts as ordinary viewers, then send donations accompanied by hidden promotional messages containing gambling content. This action causes streamers to suffer losses, both morally and socially. This condition shows that streamers need legal protection. Legal protection for streamers can be divided into two forms, namely preventive, which is realized through the implementation of policies that emphasize the state's responsibility in monitoring the misuse of donation features and the formation of regulations that are in line with developments in digital technology. Meanwhile, repressive measures are carried out through law enforcement against perpetrators of the dissemination of gambling content and illegal promotions in the digital space. Based on the results of the study, the Indonesian legal system has provided a sufficient normative framework to protect streamers, but there are no specific rules governing the form of legal protection for streamers who are victims of donation feature abuse. Therefore, more stringent and responsive regulations are needed in response to developments in digital technology to provide legal certainty and comprehensive legal protection for streamers.